Integrative multi-omics stratification and translational evaluation of Treg-targeted combination immunotherapy in breast cancer - Kim, Nari; Na, Seongwon; Lee, Hyo Jin; Yi, Woojin; Son, Ga Won; Park, Jin; Jang, Jisung; Kim, Mihyun; Jeong, Seong-Yun; Kim, Kyung Won (Frontiers in Oncology, 2026)
BackgroundImmunosuppressive breast cancer subtypes driven by regulatory T cells (Tregs) remain under-characterized, limiting precise identification of patients who may benefit from immunomodulatory therapies. Tregs are key mediators of immunosuppression within the tumor microenvironment (TME) and are closely associated with resistance to immune checkpoint inhibitors (ICIs). Therefore, defining and characterizing tumors with predominant Treg-mediated immunosuppression is essential for optimizing the use of Treg-targeted and combination immunotherapies.MethodsWe applied an unsupervised multi-omics integration approach across four molecular layers — mRNA, miRNA, DNA methylation, and proteomics —to identify immunologically distinct subtypes of breast cancer. Autoencoder-based dimensionality reduction followed by consensus clustering revealed a subgroup characterized by high Treg infiltration and immunosuppressive signaling, referred to as the Treg-enriched subtype. To evaluate therapeutic strategies, we employed a spatial quantitative systems pharmacology (spQSP) model simulating tumor–immune dynamics and tested Treg-targeted and PD-1 blockade therapies both alone and in combination. In vivo efficacy studies were conducted using the EMT6 syngeneic breast tumor model, characterized by an immunosuppressive tumor microenvironment, assessing the antitumor effects of a CCR8-targeted small molecule (IPG7236) as monotherapy or in combination with anti–PD-L1 treatment.ResultsThe C2 cluster exhibited elevated Treg-related signatures and a highly immunosuppressive tumor microenvironment. A similar Treg-enriched cluster was also identified in an independent cohort, supporting the robustness and clinical relevance of this immunosuppressive subtype. In-silico simulations performed under a C2-like, immunosuppressive context predicted that combining Treg-targeted therapy with PD-1 blockade would substantially enhance immune activation and tumor control compared with monotherapy. To experimentally validate these predictions, combination treatment of a CCR8 inhibitor (IPG7236) and anti–PD-L1 antibody demonstrated greater tumor growth inhibition than either monotherapy in the EMT6 model, confirming the predicted therapeutic synergy in Treg-enriched, immune-suppressive tumors.ConclusionThis study identifies Treg-enriched and immunosuppressive breast cancer subtype through integrative multi-omics analysis and demonstrates, through both in-silico and in-vivo approaches, the therapeutic potential of combining Treg-targeted and PD-L1 blockade therapies. These findings highlight Treg-mediated immunosuppression as a key determinant of therapeutic responsiveness, providing a biological rationale for patient stratification and guiding the development of personalized combination strategies for clinical translation.